2013
DOI: 10.1158/1538-7445.am2013-lb-80
|View full text |Cite
|
Sign up to set email alerts
|

Abstract LB-80: ATRX loss refines the classification of anaplastic glioma and is a favorable prognostic marker.

Abstract: Mutation / loss of ATRX expression has been described in anaplastic gliomas. The present study explored the role for ATRX status in the molecular classification of anaplastic gliomas and the impact of ATRX status on survival in the biomarker cohort of the NOA-04 trial. Patients (n=123) of the NOA-04 trial were analyzed for ATRX expression using immunohistochemistry. ATRX status was correlated with age, reference histology, IDH, 1p/19q and MGMT status, and the efficacy endpoints of the NOA-04 tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…ATRX is suggested to be a suppressor of the ALT pathway [ 47 ]. Cohorts of different malignancies have shown that ATRX alterations have prognostic value [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…ATRX is suggested to be a suppressor of the ALT pathway [ 47 ]. Cohorts of different malignancies have shown that ATRX alterations have prognostic value [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%